High Technologies as an Element of Crisis Management in the Context of Informational Externals (Economics and region, 2023)
In the rapidly evolving landscape of modern businesses, the role of high technologies in crisis management becomes paramount. This paper delves into the strategic integration of high technologies within crisis management frameworks, particularly in the face of informational externalities. The study emphasizes the criticality of Information Technology (IT) tools in enhancing communication, data management, marketing strategies, process optimization, and information security. The paper explores the synergy between virtualization, predictive analytics, NoSQL databases, knowledge discovery tools, and real-time data processing. It investigates how these technologies enable businesses to efficiently handle large volumes of data, foresee future scenarios, and navigate through crises. Emphasis is placed on the integration of non-relational databases (NoSQL) for reliable and scalable data management and the use of knowledge discovery tools to extract meaningful insights from diverse data sources. Furthermore, the study sheds light on the challenges posed by the global proliferation of distributed computing environments, emphasizing the risks associated with IT disruptions, cyber threats, and software vulnerabilities. The research advocates for a proactive approach to information security, particularly in the realms of internet communication, electronic mail, and web servers, crucial elements for planning effective crisis management, especially in the face of information warfare. This comprehensive analysis not only provides an in-depth understanding of the technological tools available for crisis management but also offers strategic insights for businesses to proactively adapt to the challenges posed by informational externalities. By harnessing the power of high technologies, companies can fortify their resilience, ensuring sustainable operations even in the face of unforeseen crises. This comprehensive analysis not only provides an in-depth understanding of the technological tools available for crisis management but also offers strategic insights for businesses to proactively adapt to the challenges posed by informational externalities. By harnessing the power of high technologies, companies can fortify their resilience, ensuring sustainable operations even in the face of unforeseen crises. Additionally, this research aims to encourage further exploration and innovation in the realm of high technology solutions for crisis management, fostering a future where businesses can confidently navigate the complex landscape of informational externalities with cutting-edge tools and strategies.
Keywords: crisis management; information technology; communication; process optimization; information security